HUBUNGAN ANTARA USIA DAN RIWAYAT PENYAKIT IBU DENGAN KEJADIAN BBLR DI RUMAH SAKIT Dr. SOEDIRAN MANGUN SUMARSO WONOGIRI - Kristiningtyas, Y. Wahyunti; Aprila, Rani (Akademi Keperawatan Giri Satria Husada Wonogiri, 2020)
Low Birth Weight Infants (LBW) are newborns weighing less than 2500 grams. Divided into: preterm babies, namely babies with a gestation period of less than 37 weeks, term babies, namely babies with a gestation period starting from 37-42 weeks, babies over months, namely babies with a gestation period starting from 42 weeks or more Low birth weight can be caused by several factors, including; maternal factors such as illness, maternal age, social conditions, fetal factors such as multiple pregnancy, chromosomal abnormalities and environmental factors such as radiation exposure, exposure to toxic substances. Some of the short-term problems caused by LBW cases are metabolic disorders, immunity disorders, respiratory problems, circulatory disorders and electrolyte fluid disorders. Problems that arise in infants with low birth weight are hypothermia, hyperglycemia, hypoglycemia, jaundice, respiratory disorders, circulatory disorders, indigestion and elimination disorders. The purpose of this study was to determine the relationship between age and history of maternal disease with the incidence of low birth weight at dr. Soediran Mangun Sumarso. This type of research is an analytic survey with a cross sectional approach. The population in this study is the number of mothers giving birth from January to May 2019 as many as 292. The sample in this study was 72 mothers giving birth. The sampling technique used was simple random sampling. The instrument used in this study was a questionnaire. The data analysis used was univariate analysis to determine the frequency distribution of each variable and bivariate analysis using the Chi Square test. The results showed that most mothers (54.2%) had an age between 20 to 35 years. Most (52.8%) mothers had a history of disease. Most (60.5%) history of disease accompanying the mother's pregnancy was anemia. Most of the mothers (51.4%) of their babies did not experience LBW. There was a significant relationship between maternal age and the incidence of LBW (p = 0.002) and there was a significant relationship between maternal disease history and the incidence of LBW at RSUD Dr. Soediran Mangun Sumarso Wonogiri (p = 0.004) with OR = 4.615.Â